Self-efficacy moderation and mediation roles on BPSD and social support influences on subjective caregiver burden in Chinese spouse caregivers of dementia patients. (September 2014) - Zhang, Shuying; Guo, Qihao; Edwards, Helen; Yates, Patsy; Li, Chunbo
ABSTRACT Background: This study aims to explore moderation and mediation roles of caregiver self-efficacy between subjective caregiver burden and (a) behavioral and psychological symptoms (BPSD) of dementia; and (b) social support. Methods: A cross-sectional study with 137 spouse caregivers of dementia patients was conducted in Shanghai. We collected demographic information for the caregiver–patient dyads, as well as information associated with dementia-related impairments, caregiver social support, caregiver self-efficacy, and SF-36. Results: Multiple regression analysis showed that caregiver self-efficacy was a moderator both between BPSD and subjective caregiver burden, and social support and subjective caregiver burden. Results also showed a partial mediation effect of caregiver self-efficacy on the impact of BPSD on subjective caregiver burden, and a mediation effect of social support on subjective caregiver burden. Caregiver self-efficacy and subjective burden significantly influenced BPSD and social support. Conclusion: Caregiver self-efficacy played an important role in the paths by which the two factors influenced subjective burden. Enhancing caregiver self-efficacy for symptom management (particularly BPSD) can be an essential strategy for determining interventions to support dementia caregivers in China, and possibly in other countries.